CHROMIUM (III) ADSORPTION FROM AQUEOUS SOLUTION BY Rhizophora apiculata TANNINS - C. W. Oo; K. Jain (Indonesian Journal of Chemistry, 2007)
Adsorption of Cr3+ from aqueous solution by Rhizophora apiculata tannins was investigated in batch shaking experiments. Tannins extracted from R. apiculata mangrove barks was chemically modified with formaldehyde in the basic solution of sodium hydroxide. The performance of the produced adsorbent on the adsorption of Cr3+ was evaluated based on the effect of several parameters like initial pH, adsorbent dosage, initial Cr3+ concentration and contact time. Equilibrium adsorption data was analyzed by Langmuir, Freundlich, Sips and Dubinin-Raduskhevich (D-R) isotherms. The fitness of the isotherms to the experimental data was determined by non-linear regression analysis. Adsorption capacity calculated from Langmuir isotherm was found to be 10.14 mg Cr3+/g of adsorbent at optimum adsorption pH of 4.5. Mean energy of adsorption with the value of 10.35 kJ/mol indicated that adsorption Cr3+ on Rhizophora apiculata tannins followed ion-exchange reaction. Kinetic study showed that the adsorption process followed the pseudo second-order kinetic model.